(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
This article, entitled "Venezuelan Rural Primary Education: A Phenomenological Study from the Teachers’ Perspective," aims to uncover, understand, and interpret the pedagogical, creative, and adaptive strategies implemented by teachers to ensure educational continuity and relevance. It also seeks to generate emerging theoretical constructs on the existential pedagogical resilience of rural teachers, contributing to a theory of Venezuelan rural education. The research was framed within the interpretive paradigm, employing the phenomenological-hermeneutic method. This qualitative approach allowed for a deep immersion in the teachers’ narratives. Data collection was based on testimonies and interviews, seeking the essence of lived experience to construct a humanized vision of teaching practice. The results revealed that the teacher’s pedagogical resilience is articulated through radical adaptation and forced creativity. The teacher is conceived not only as an instructor but also as a psychosocial leader who sustains the social fabric. The research concludes that rural primary education in Venezuela is sustained by the ethics of care and the existential tenacity of its teachers. It is imperative that policies recognize and validate the human and social capital that these teachers represent. The need to develop theoretical frameworks and training programs that draw upon this contextualized resilience is proposed, guaranteeing the system’s sustainability through the comprehensive strengthening of the teaching role.